Isotopic tracing of the impact of mobility on infectious disease: The origin of people with treponematosis buried in hull, England, in the late medieval period. Issue 2 (24th December 2012) - Roberts, C.A.; Millard, A.R.; Nowell, G.M.; Gröcke, D.R.; Macpherson, C.G.; Pearson, D.G.; Evans, D.H.
Abstract Treponematosis has been one of the most studied and debated infectious diseases in paleopathology, particularly from the standpoint of its origin, evolution, and transmission. This study links evidence for treponematosis in skeletons from the 14th–16th century AD cemetery of the Augustinian friary of Hull Magistrates Court, England, with data from stable isotope analysis to test the hypothesis that the people with treponemal disease buried at this site were not locally born and raised. The objective is to explore the potential of using stable isotope data to track the place of origin and extent of mobility of individuals with an infectious disease. Dental enamel samples of 12 skeletons were selected for strontium (87Sr/86Sr ratio) and oxygen (δ18O) stable isotope analysis based on the presence (six ‐ diseased) or absence (six ‐ controls) of bone changes associated with treponemal disease. The oxygen isotope ratios of all but three individuals (1047, 1121, 823) overlapped at two standard deviations with the inferred local precipitation range, and only one individual (1216) had a strontium isotope ratio outside the regional range. Two of the four had probable/possible treponemal bone changes. Those with treponemal bone changes were not demonstrably more likely to be migrants than those without such lesions. However, because of extensive documentary evidence for trade with the Baltic Sea area, and for merchants from towns such as Stralsund, Danzig and Elbing being in Hull, it is very plausible that the four migrants came from the Baltic area or even southern Sweden. Am J Phys Anthropol, 2013. © 2012 Wiley Periodicals, Inc.